Quality of Work Life of People Aged 40 and Over but Younger Than 60 in Songkhla Province Influencing Needs for Health Services When They Were Elderly People - Hungsapruek, Theerawat (Journal of Business, Innovation and Sustainability (JBIS), 2022)
This research was useful for Prince of Songkla University, Hat Yai Campus because it could be used as guidelines to organize health services for the elderly and as information for public and private organizations undertaking elderly care missions to seek people to take care of the elderly. They also recognized the needs for the elderly care organization and what kind of health services people needed when they became elderly. Therefore, the right investment would be made in preparation to promote a good quality of life so that people continued to have good health. The research aimed to study 1) the level of work-life quality, 2) the level of health service needs of people aged 40 and over but younger than 60 when they became elderly, and 3) the level of work-life quality of those people in Songkhla Province which influenced health care needs when they became elderly people. The study was a quantitative research. The sample group consisted of the total of 410 Songkhla people aged 40 years old and over but younger than 60 years of age. Multiple regression statistics was used in the study. The results were as follows: 1) The quality of work life of people aged 40 years and over but younger than 60 years old in Songkhla Province was at a high level (Mean = 3.67) 2) When they were elderly, people aged 40 years and over but younger than 60 years old had a high level of health care needs (Mean = 3.71) 3) Quality of work life in term of the balance between work and personal life of people aged 40 years and over but younger than 60 years had the highest influence on health services when they became elderly.